2014
DOI: 10.3233/jad-140867
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns and Cognitive Dysfunction in a 12-Year Follow-up Study of 70 Year Old Men

Abstract: We found no strong associations with development of cognitive dysfunction for any of the dietary patterns investigated. However, there was a potentially beneficial association for a Mediterranean-like diet on the development of cognitive dysfunction in the subpopulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
102
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(106 citation statements)
references
References 55 publications
3
102
1
Order By: Relevance
“…One study assessed dietary intake with a 24-h recall and a food-composition table that contained ;900 food and drink items (38). Another study used a 7-d food record and a validated precoded menu book (40), and a Health Habits and History Questionnaire including 128 food and drink items was used in one study (54) (Supplemental Table 2). …”
Section: Resultsmentioning
confidence: 99%
“…One study assessed dietary intake with a 24-h recall and a food-composition table that contained ;900 food and drink items (38). Another study used a 7-d food record and a validated precoded menu book (40), and a Health Habits and History Questionnaire including 128 food and drink items was used in one study (54) (Supplemental Table 2). …”
Section: Resultsmentioning
confidence: 99%
“…Next, 307 of the 333 articles were excluded after reading the titles and abstracts, and the remaining 26 full-text articles were estimated for eligibility. Finally, 9 articles were included in the present systematic review and meta-analysis131415161718192021. Reasons for the exclusion of the 17 articles were listed in Supplementary Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…Mediterranean diet (characterizes by a high consumption of fruit, vegetables, legumes, cereals, and unsaturated fatty acids; low consumption of meat and saturated fatty acids; low to moderate consumption of dairy products; moderate to high consumption of fish; and a regular but moderate drinking of alcohol) is reported to have a protective effect of cognitive decline in a substantial number of qualitative researches5678 and quantitative reviews9101112. Recently, 4 cohort studies have been published on this topic, and these high-quality articles included an additional 25,864 participants13141516. However, the findings of the 4 studies were inconsistent, and 2 of these studies observed a non-significant association between Mediterranean diet and cognitive disorders1315.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cases of dementia without neuroimaging or sufficient clinical details in medical records to set a specific subtype diagnosis were classified as unspecified dementia (34). Allcause dementia included AD, vascular dementia, frontotemporal dementia (38), Lewy body dementia (39), unspecified dementia, and Parkinson disease with dementia (38,40).…”
Section: Dementia Diagnosesmentioning
confidence: 99%